Creative thinking and psychological adjustment in students of technical higher education institution - Ruzmetova Sayyorakhan Timurkhanovna; Gulomjonov Botirjon Gulomjon ogli (Academia One Publishing, 2025)
In this article, technical education is essential for fostering innovation and problemsolving abilities among students. However, students in technical higher education institutions often face psychological challenges, including stress, anxiety, and social isolation, which can hinder their academic and personal growth. This paper explores the role of creative thinking in technical education, emphasizing its significance in developing innovative solutions and critical decision-making skills. Additionally, it examines the psychological adjustment challenges faced by technical students, such as workload pressure, impostor syndrome, and burnout. The paper also proposes strategies for enhancing both creative thinking and psychological adjustment, including integrating creativity into the curriculum, providing mental health support, promoting work-life balance, and fostering a growth mindset. By implementing these strategies, technical institutions can create an environment that supports students’ well-being and professional success, equipping them with the skills needed to thrive in their careers.
Keywords: Creative thinking; critical thinking; psychological adjustment